Marvel-verse. Black Widow. - Sumerak, Marc; Tobin, Paul, 1965-; Nicieza, Fabian; Slott, Dan (Marvel Worldwide, Inc, 2020)
Compilation of seven stories in Marvel's Black Widow comic series, in which the superhero spy teams up with other Avengers to protect innocent victims, infiltrate enemy headquarters, and uncover double agents.